The Prince of Wales : a biography - Dimbleby, Jonathan (New York W. Morrow, 1994)
A biography of Charles, the Prince of Wales, who is heir to the British throne. Discusses the role of the monarchy and its relationship to the government, armed services, and Church in today's England.
Keywords: Charles, -- Prince of Wales, -- 1948- Princes -- Great Britain -- Biography. Princes